SUMBER DAYA INTERNAL PERUSAHAAN SEBAGAI DETERMINAN KINERJA KEUANGAN - Natalia, Irene; Jusuf, A An Arief (Journal of Innovation Research and Knowledge, 2024)
This study examines the influence of intrinsic company factors on the financial performance of transportation and logistics sector companies listed on the Indonesia Stock Exchange from 1994 to 2022. The intrinsic management factors include company size, liquidity, corporate income tax, intangible assets, leverage, and company age. Data were taken from the OSIRIS database and tested using 332 observations were obtained. The analysis was tested with ordinary least squares. The study found that intangible assets and leverage affect financial performance. This research contributes to the resource-based theory regarding management's use of company resources to generate financial performance. The intrinsic company variables, such as intangible assets and leverage, should be considered by investors when assessing financial performance and making investment decisions in transportation and logistics sector companies in Indonesia, especially during the health crisis period. Additionally, management needs to maintain profitability levels to achieve future sustainability and solvency.